2000
DOI: 10.1007/s11743-000-0133-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial aspects of linear alkylbenzene sulfonate degradation in coastal water

Abstract: Viable and total bacteria were determined during linear alkylbenzene sulfonate (LAS) degradation in coastal seawater. Viable bacteria were determined by plate counts on marine agar media, while total bacteria were determined by flow cytometry after SYTO-13 staining. LAS degradation was monitored by high-performance liquid chromatography analysis. Seawater samples with LAS at 5 mg/L, incubated in the laboratory (20°C, 100 rpm, 30 d), showed in most cases a similar evolution in bacterioplankton abundance over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Nevertheless, although the aerobic biodegradation of LAS in seawater is evidently relevant, studies of this process are scarce (e.g., refs 6−13 ); those conducted are limited to monitoring its primary biodegradation (i.e., the disappear ance of the surfactant) or to its mineralization in estuaries (). The primary degradation and mineralization kinetics for LAS under aerobic conditions have previously been characterized in continental ( , ), estuarine ( , ), and marine waters ( ). Some of the mathematical equations that have been proposed to describe the kinetics of the process are based on curve fitting of the experimental substrate consumption or CO 2 production during biodegradation ().…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although the aerobic biodegradation of LAS in seawater is evidently relevant, studies of this process are scarce (e.g., refs 6−13 ); those conducted are limited to monitoring its primary biodegradation (i.e., the disappear ance of the surfactant) or to its mineralization in estuaries (). The primary degradation and mineralization kinetics for LAS under aerobic conditions have previously been characterized in continental ( , ), estuarine ( , ), and marine waters ( ). Some of the mathematical equations that have been proposed to describe the kinetics of the process are based on curve fitting of the experimental substrate consumption or CO 2 production during biodegradation ().…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable variability among studies in all 4 surfactants (shown by large data ranges), with many studies revealing marine surfactant biodegradation to be a long process. It is argued that such data variability may be explained by natural variation (between different environments) and microbial variation by different pretreatment methods (e.g., acclimation history of associated microbial communities to surfactants ), humic substance association, cometabolic transformation, or nutrient‐level variation . Primary biodegradability of LAS homologs has been shown to increase with alkyl chain length , although Larson et al found that LAS mineralization was relatively unaffected by such structural differences.…”
Section: Fatementioning
confidence: 99%
“…The flow rate was set to 1ml per minute. Data acquisition and processing were performed by using LC solution system (Shimadzu) [15].…”
Section: Measurement Of Las Degradationmentioning
confidence: 99%